2001
DOI: 10.1128/jvi.75.5.2377-2387.2001
|View full text |Cite
|
Sign up to set email alerts
|

Using Recombinant Coxsackievirus B3 To Evaluate the Induction and Protective Efficacy of CD8+T Cells during Picornavirus Infection

Abstract: Coxsackievirus B3 (CVB3) is a common human pathogen that has been associated with serious diseases including myocarditis and pancreatitis. To better understand the effect of cytotoxic T-lymphocyte (CTL) responses in controlling CVB3 infection, we have inserted well-characterized CTL epitopes into the CVB3 genome. Constructs were made by placing the epitope of interest upstream of the open reading frame encoding the CVB3 polyprotein, separated by a poly-glycine linker and an artificial 3C pro /3CD pro cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 53 publications
5
86
2
Order By: Relevance
“…In contrast to lymphocytic choriomeningitis virus infection, CVB3 infection caused minimal activation of T-cell responses in either WT or TIMP-1KO mice ( Figure 3A). This is consistent with a previous study showing that recombinant CVB3 induced very weak CD8 ϩ T-cell responses, 25 and others have reported that the 3A protein of the closely related poliovirus can interrupt trafficking of MHC class I molecules, 26 which is required for epitope presentation to CD8 ϩ T cells. In addition, and as was observed for CD8 ϩ T cells, the CD4 ϩ T-cell responses to CVB3 infection were similar in WT and TIMP-1KO mice ( Figure 3B).…”
Section: T-cell Activation After Cvb3 Infection Is Minimal and Is Simsupporting
confidence: 82%
“…In contrast to lymphocytic choriomeningitis virus infection, CVB3 infection caused minimal activation of T-cell responses in either WT or TIMP-1KO mice ( Figure 3A). This is consistent with a previous study showing that recombinant CVB3 induced very weak CD8 ϩ T-cell responses, 25 and others have reported that the 3A protein of the closely related poliovirus can interrupt trafficking of MHC class I molecules, 26 which is required for epitope presentation to CD8 ϩ T cells. In addition, and as was observed for CD8 ϩ T cells, the CD4 ϩ T-cell responses to CVB3 infection were similar in WT and TIMP-1KO mice ( Figure 3B).…”
Section: T-cell Activation After Cvb3 Infection Is Minimal and Is Simsupporting
confidence: 82%
“…Deletion of a foreign epitope is not unique to JHM because an inserted CD8 T cell epitope was also deleted from recombinant Coxsackie B virus by day 4 p.i. (39) and from recombinant polioviruses after passage through tissue culture cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve BALB/c mice were infected intraperitoneally with 5 ϫ 10 3 PFU of the P1 stock of Koz1 virus. Three of the mice died within 2 days of infection, indicating that this mutant virus was highly pathogenic; this finding contrasts with the severe attenuation of most recombinant coxsackieviruses, in which doses as high as 10 7 PFU may be nonlethal (40). The hearts and pancreata of the nine surviving mice were harvested for analyses at 2, 5, and 9 days postinfection (four, three, and two mice, respectively).…”
Section: Vol 79 2005 Eukaryotic Translational Initiation Motif In Cmentioning
confidence: 99%
“…In brief, uncapped RNA was produced by using the MAXIscript kit (Ambion). For the translation, 65% of S10 extract from HeLa cells, 1ϫ "all four" buffer (10ϫ buffer composed of 300 l of 1 M creatine phosphate; 300 l of 2 M potassium acetate; 100 l of creatine kinase [40 The translation was performed at 30°C for 4 h, after which 2ϫ Laemmli sample buffer was added, and the reactions were heated to 90°C for 5 min. Then, 5-l portions of the reactions were loaded and run on a sodium dodecyl sulfate-12.5% polyacrylamide gel.…”
Section: In Vitro Translationmentioning
confidence: 99%